STUDI MINAT MEMBACA SISWA MIN 12 BEREUEN- ACEH - Srie Faizah Lisnasari (PGSD Universitas Negeri Medan, 2018)
This study aims to explore further information about the factors that influence the low interest in scholarships at the MIN 12 Bereuen-Aceh School. The population of this study was students MIN 12 Bireuen class VI. The sampling technique is done using the simple random sampling method. The data collection technique used in this study is the Inventory of Student Interest in Safran Model (Safran Students Interest). The results showed that from 32 respondents the following data were obtained: (1) Interest in reading students MIN 12 Bireuen-Aceh, generally included in the medium category with details: 18 0rang (54.54%) often went to the library, 13 people (39.39%) sometimes to the library and only 2 people (6.06%) always go to the library; (2) Students visit the library: 19 people (57.57%) sometimes, 14 people (42.42%) always and 1 person (3.03%) never go to the library; (3) The frequency of student visits to the library is generally 1-3 times in 1 week, which is 31 people (93.93%) from the sample and; (4) visiting the library to search for or read books if: a) there are assignments given by the teacher which are 15 people (45.45%), 6 people (18.18%) take advantage of free time to read books or intense library visits and only 1 person (3.03 %) because of hobbies.Keywords: Study, Reading Interest, MIN 12 Bireuen